Integrando desiguais: Assimetrias estruturais e políticas de integraç\~ao no Mercosul - André de Mello e Souza; Ivan Tiago Machado Oliveira; Samo Sérgio Gonçalves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– Structural asymmetries between countries - understood as those which originate from differences in economic size, geographical position, factor endowments, access to regional infrastructure, institutional quality and level of development - constitute one of the main challenges to the regional integration process promoted by Mercosur. The greater size and diversification of the Brazilian economy relative to those of the other members of the bloc (and above all Uruguay and Paraguay) render the common external tariff of Mercosur a reflection of the tariff structure and commercial interests of Brazil, thereby undermining the creation of a complete customs union. Furthermore, they also reduce the possibilities of creating supranational institutions, or at least institutions less vulnerable to changes in national governments. This paper presents indicators of structural asymmetries in Mercosur and analyses the policies adopted to compensate for such asymmetries. It offers evidence that, despite its greater and more diversified economy, Brazil falls behind both Argentina and Uruguay with respect to per capita income and indicators of human development and socio-economic inequality. Moreover, Brazilian subnational regions are the least developed in Mercosur, and Brazil has not played the role of buyer of last resort in the process of regional integration, presenting generally surpluses with its trade partners in the bloc. The Structural Convergence Fund of Mercosur (known by the Portuguese acronym Focem) is crucial though insufficient for the compensation of structural asymmetries within Mercosur. Proposals for improving and expanding Focem are presented, notably those that defend the eligibility of projects from the private sector, the employment of more technical rather than political criteria in the selection of these projects, the provision of assistance for the elaboration of projects in smaller countries, greater transparency in the allocation of resources and in the announcement of the project results, and, finally, the use of the Fund to promote macroeconomic harmonization as well as social cohesion in the least developed subnational regions.
Keywords: F15; F59; 330; Politische Integration; Mercosur-Staaten